2018
DOI: 10.1631/jzus.b1700086
|View full text |Cite
|
Sign up to set email alerts
|

Creation of a rabbit model for intrauterine adhesions using electrothermal injury

Abstract: The pathogenesis and therapeutic treatment of intrauterine adhesions (IUAs) remain unsolved, highlighting the need for stable and effective experimental animal models. In this study, uterine electrocoagulation of twenty-one female New Zealand White rabbits was carried out to establish an IUA model. As rabbits have two completely separate uterine horns, each rabbit had its own internal control: one uterine horn was given an electrothermal injury (Group A, n=21), and the contralateral uterine horn received no tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Animal models of intrauterine adhesions (IUA) have been established using various species, such as mice, rats, New Zealand white rabbits, beagles, and rhesus monkeys, with different modeling approaches [ 18 , [20] , [21] , [22] , [23] , [24] ]. Among these options, the rat has emerged as the most commonly used model due to its distinct genetic background, robust reproductive capabilities, uncomplicated dietary needs, cost-effectiveness, spontaneous ovulation, and regular estrous cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal models of intrauterine adhesions (IUA) have been established using various species, such as mice, rats, New Zealand white rabbits, beagles, and rhesus monkeys, with different modeling approaches [ 18 , [20] , [21] , [22] , [23] , [24] ]. Among these options, the rat has emerged as the most commonly used model due to its distinct genetic background, robust reproductive capabilities, uncomplicated dietary needs, cost-effectiveness, spontaneous ovulation, and regular estrous cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these, a variety of injury methods for establishing the IUA models have been proposed, which included mechanical damage by curets or scalpels, electrical burns, chemical damages, lipopolysaccharides-induced and various combination methods [ [15] , [16] , [17] , [18] ]. However, the majority of these methods are intricate and unstable.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, one side of the uterus was perfused with 95% ethanol as the injured group and the other side was perfused with saline as a control group. As shown in Figure 3, it was found that the structure of the endometrium was destroyed after ethanol perfusion, and has a similar pathological feature as physical [6, 25] or drug stimulation [26]. Therefore, the thickness of the endometrium, the lumen area of the uterus, and several superficial folds were selected as the quantitative indexes to evaluate the imaging efficiency of OCT/US imaging efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, establishing an accurate animal model is essential for studying the mechanism, prevention, and treatment of IUA. The existing IUA modeling methods include mechanical damage with various homemade curettes and scalpels, electrical burns, chemical damage from alcohol or LPS, and a combination of several approaches (32,36,37). Among them, the most used is the MDLI-IUA model (38).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical damage-lipopolysaccharide (LPS) infection (MDLI) IUA mouse model was established using dual methods using uterine curettage and LPS injection as previously described (32). All mice were anesthetized with isoflurane and placed in the supine position.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%